2023
DOI: 10.1108/ijchm-08-2022-1031
|View full text |Cite
|
Sign up to set email alerts
|

Can perceived coolness enhance memorable customer experience? The role of customer engagement

Abstract: Purpose Memorable customer experience (MCE) is a key factor affecting customer loyalty and revisit intention. Hospitality managers must identify factors that create MCEs. This study aims to investigate relationships among perceived coolness, customer engagement and MCE and examine the mediation effect of customer engagement. Design/methodology/approach Two samples of 434 restaurant customers and 372 hotel customers in Taiwan returned questionnaires. Hypotheses were examined by structural equation modeling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 72 publications
0
8
0
1
Order By: Relevance
“…In this study, as mentioned previously, cool hospitality brands are perceived to be more consistent and aligned with AI. This is because they are known for their extraordinary environments, innovative atmospheres and adaptability to change (Suzuki and Kanno, 2022;Tsaur et al, 2023). AI technology conveys qualities such as technological innovation, efficiency, an extraordinary image and a high-tech experience to consumers (Guerreiro and Loureiro, 2023;Ozdemir et al, 2023).…”
Section: The Mediating Role Of Feeling Rightmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, as mentioned previously, cool hospitality brands are perceived to be more consistent and aligned with AI. This is because they are known for their extraordinary environments, innovative atmospheres and adaptability to change (Suzuki and Kanno, 2022;Tsaur et al, 2023). AI technology conveys qualities such as technological innovation, efficiency, an extraordinary image and a high-tech experience to consumers (Guerreiro and Loureiro, 2023;Ozdemir et al, 2023).…”
Section: The Mediating Role Of Feeling Rightmentioning
confidence: 99%
“…Regarding the influence of brand coolness, research has highlighted its positive effects on consumer psychology and behavior. For example, studies have found that brand coolness is associated with customer experience (Tsaur et al , 2023), willingness to pay (Koskie and Locander, 2023), purchase intention (Khoi and Le, 2022; Suzuki and Kanno, 2022), brand attitude (Chen et al , 2023), brand love (Khoi and Le, 2022; Tiwari et al , 2021) and brand loyalty (Jiménez-Barreto et al , 2022). These findings underscore the significant role of brand coolness in shaping consumer behavior within the hospitality industry.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Müşterilerin deneyimlerinin olumlu, tatmin edici ve hatırlanabilir olması tekrar ziyaret niyetlerini (Chen ve Rahman, 2018;Kim, 2017;Tsaur, Teng, Han ve Tu, 2023;Wong, Lai ve Tao, 2019;Zhang, Wu ve Buhalis, 2018) ve ağızdan ağıza iletişim niyetlerini (Kim, 2017;Wong vd., 2019) etkilemektedir. Bu bağlamda, tüketicilerin bilgi arama süreçleri değerlendirildiğinde, hatırlanabilir turizm deneyimlerinin hem içsel hem de dışsal bilgi kaynakları aracılığıyla mevcut ve potansiyel müşterilerin satın alma karar süreçleri üzerinde etkili olduğu söylenebilmektedir.…”
Section: Introductionunclassified
“…Customer engagement can be described from a behavioral manifestation as customers' non-transactional behaviors, including two well-explored types—customer's social influence engagement and knowledge-sharing engagement ( Kumar & Pansari, 2016 ; Li et al, 2021 , 2021 , 2021). Existing literature indicates that consumer engagement can enhance customer-perceived value ( Touni et al, 2022 ), foster memorable customer experiences ( Tsaur et al, 2023 ), and strengthen brand loyalty ( Li et al, 2020 ). Consequently, it is frequently adopted as a pivotal metric for assessing the efficacy of brand communication strategies, particularly in social media dissemination ( Wang et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Restaurants can obtain more value from the consumer by cultivating customer engagement ( Shin, 2023 ). Accordingly, cultivating customer engagement through online communities is important for restaurants ( Tsaur et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%